Investigation of Advantages and Disadvantages of Percutaneous and Surgical Tracheostomies - Cemal Hacı; Reşit Murat Açıkalın; İbrahim Akkoç; Mehmet Toptaş (Haseki Tıp Bülteni, 2018)
Aim: In our study, we aimed to evaluate surgical tracheostomy and percutaneous tracheostomy and to investigate their complications. Methods: In this study, we retrospectively evaluated medical records of 56 patients who underwent percutaneous tracheostomy (n=24) and surgical tracheostomy (n=32) in the otorhinolaryngology and anesthesiology clinics at our hospital. Results: Fifty six patients evaluated and there was no statistically significant difference in terms of indications for tracheostomy between the groups. The duration of surgical tracheostomy was 21.2±2.9 minutes and that of percutaneous tracheostomy was 12.4±3.2 minutes and the difference was found to be statistically significant (p<0.001). Conclusion: Both surgical tracheostomy and percutaneous tracheostomy are safe and practiced methods. The duration of percutaneous tracheostomy was shorter than surgical tracheostomy in our study. Percutaneous tracheostomy is a method that can be safely performed.